Design, analysis and fabricate solar car chasis and body (race type) - Muhamad Fikri, Abd Rahman (2011)
This thesis present about design and analysis solar car chassis and body. The objective of this project is to design analysis and fabricate the elements of body and chassis of a race type solar car for the target of the most lightweight and lowest material cost design. The solar car chassis was design using Solid Work 2010. Aluminum alloy AA6063-T6 was used as a material for solar car chassis. Two designs of solar car chassis were analyzed. The finite element modeling and analysis were performed using ALGOR software for analysis the solar car chassis. The maximum displacement magnitude, worst stress and worst strain was compare between solar car chassis Design 1 and Design 2. The solar car body is developing using Solid Work 2010. Fiberglass and alumunium sheet was used as a material for solar car body. Three designs of solar car body were analyzed. The computational fluid dynamic was performed using COSMOSFLOWORK software for analysis the solar car body. The pressure at front, rear and drag force was compare between solar car body Design 1, Design 2 and Design 3. As conclusion the best design for chassis is solar car chassis Design 2 and the best for body is solar car body Design 3.The solar car chassis design 2 have minimum displacement, worst strain and worst stress. The solar car body design 3 have minimum drag force and pressure at front of the body.